A Grid-Connected Solar PV/Wind Turbine Based Hybrid Energy System Using ANFIS Controller for Hybrid Series Active Power Filter to Improve the Power Quality. (14th November 2022) - Cholamuthu, Pazhanimuthu; Irusappan, Baranilingesan; Paramasivam, Suresh Kalichikadu; Ramu, Senthil Kumar; Muthusamy, Suresh; Panchal, Hitesh; Nuvvula, Ramakrishna S S; Kumar, Polamarasetty P; Khan, Baseem
Abstract : The current needs of more nonlinear loads and the frequent usage of single-phase loads in three-phase system drastically create power quality issues in the grid-connected system. As a consequence, it creates an undesirable power quality issue (PQI) in the form of a change in the nature of voltage and current magnitude and waveforms in the power system. The voltage-related PQI leads to a huge disturbance in the system when compared with the current-related PQI. The hybrid series active power filter provides grids with the required voltage in series and suppresses the voltage-related harmonics caused by grid-connected nonlinear loads. The present work deals with an adaptive neurofuzzy inference system controller for the generation of a reference voltage signal that uses a reduced active filter rating. The simulation study was done in the MATLAB 2020b/Simulink environment and the experimental effectiveness of the proposed ANFIS controller was compared with that of a conventional controller. In the grid-connected system, this system prevents voltage quality problems such as voltage sag, flickering, voltage swell, neutral currents, and reactive power. The renewable energy sources interfaced into the DC-link minimize short and long voltage challenges so that they improve the overall performance of the system. In accordance with IEEE standard 519-1992, a prototype model was proved to demonstrate that the power delivery system works effectively under different conditions and reduces the total harmonic distortion by approximately 30%, which is less than the 5% acceptable limit.